2015
DOI: 10.1176/appi.neuropsych.15060142
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiology of Adult ADHD: Emerging Evidence for Network Dysfunctions

Abstract: FIGURE 1. Changes in cortical thickness provide one measure of brain maturation. A large longitudinal study found that for most areas of cortex, children with attention deficit hyperactivity disorder (ADHD) reach peak cortical thickness several years later than typically developing children, supporting presence of developmental delay. 1 The rate of cortical thinning also differed between the group who continued to meet diagnostic criteria into adulthood (persistent ADHD) and those who did not (remitted ADHD). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 74 publications
(144 reference statements)
0
6
0
Order By: Relevance
“…ADHD has been thought to affect mainly during childhood and adolescence. However, there is increasing consensus in the fact that ADHD evolves throughout the patient’s lifespan rather than ceasing in adulthood (Adler & Cohen, 2004; Biederman, 2005; Jadidian, Hurley, & Taber, 2015; Young & Gudjonsson, 2008). Overall, some ADHD core symptoms tend to decline over time, and they may manifest in different forms as patients adjust their social and personal environment to the symptomatology (Adler & Cohen, 2004; Biederman, Mick, & Faraone, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…ADHD has been thought to affect mainly during childhood and adolescence. However, there is increasing consensus in the fact that ADHD evolves throughout the patient’s lifespan rather than ceasing in adulthood (Adler & Cohen, 2004; Biederman, 2005; Jadidian, Hurley, & Taber, 2015; Young & Gudjonsson, 2008). Overall, some ADHD core symptoms tend to decline over time, and they may manifest in different forms as patients adjust their social and personal environment to the symptomatology (Adler & Cohen, 2004; Biederman, Mick, & Faraone, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Decades of neuroimaging research have shown multiple ADHD-related abnormalities in brain structure and function, and suggests that ADHD may in part be due to delayed or disrupted neurodevelopment and maturation. These brain regions have been shown to be responsible for higher order executive functions; including executive control over behavior, attention, social cognition, and networks supporting primary sensory and motor functions [ 2 , 3 ]. Childhood ADHD is associated with several functional impairments including reduced school performance and academic attainment, and social rejection [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 Children with ADHD experience complications such as difficulties in peer relationships, substance abuse, and increased risk for delinquency. 6 , 7 , 8 Identifying risk factors, underlying etiology, and biological factors that may predispose children to ADHD could have great public health importance by informing prevention or treatment efforts.…”
Section: Introductionmentioning
confidence: 99%